2012
DOI: 10.1002/jsfa.5756
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical chemical characterization of phosphate‐metal–humic complexes and relationships with their effects on both phosphorus soil fixation and phosphorus availability for plants

Abstract: The results indicated the potential efficiency of PMHA-based fertilizers to optimize P fertilization for crops cultivated in soils with high P fixation ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 22 publications
0
29
0
12
Order By: Relevance
“…Esse fato pode estar relacionado com a lenta decomposição e mineralização de P desses resíduos, que favoreceu menor retenção desse nutriente no solo. Menor adsorção e maior aproveitamento de P pelas plantas foi observado por Urrutia et al (2013), quando utilizaram fertilizante fosfatado de liberação lenta.…”
Section: Ph Em áGua Nos Solos Com Fontes Inorgânicas Dos Nutrientes (unclassified
“…Esse fato pode estar relacionado com a lenta decomposição e mineralização de P desses resíduos, que favoreceu menor retenção desse nutriente no solo. Menor adsorção e maior aproveitamento de P pelas plantas foi observado por Urrutia et al (2013), quando utilizaram fertilizante fosfatado de liberação lenta.…”
Section: Ph Em áGua Nos Solos Com Fontes Inorgânicas Dos Nutrientes (unclassified
“…These studies also showed that these complexes were stable and soluble in soil solutions with pH values ranked between 4 and 8 [41,42]. Other studies showed that these humic-metal-phosphate complexes prevented phosphate soil fixation and provided available P to different plant species [46]. Therefore, the application of these types of humic-metal-phosphate complexes has great potential interest to enhance the agronomic efficiency of P-compound fertilizers.…”
Section: The Fabrication Of Humic-mineral Complexes During the Manufamentioning
confidence: 92%
“…Obtained humic-metalphosphate complexes were only partially soluble in water but totally soluble in rhizospheric root exudates and neutral ammonium citrate (an indicator of potential P availability for plants) [47,49]. The main interest of compound fertilizers based on these types of complexes is that their potential soil fixation (P retrogradation) and leaching are very low due to their low water solubility, while they are able to provide available P for plants [46,47]. However, plant roots need to interact in some way with fertilizer granule to solubilize phosphate by the action of root exudates [46,47] (Fig.…”
Section: The Fabrication Of Humic-mineral Complexes During the Manufamentioning
confidence: 99%
See 2 more Smart Citations